A implementação da Lei 10.639/2003 nas Escolas na Cidade de Brejinho de Nazaré, Tocantins. - CARVALHO, Márcio Rodrigues (Universidade Federal do Tocantins, 2023)
Law 10,639/2003 makes the teaching of Afro-Brazilian and African history and culture mandatory from Kindergarten to High School and proposes to contribute to the deconstruction of the racism that exists and is propagated by the school through a curriculum that institutionalizes racial prejudice against the black population. The general objective of this article is to analyze whether and how Law 10.639 of 2003 is applied in public schools in the municipality of Brejinho de Nazaré, considering that they have enrolled students from certified quilombola communities in the municipality, justifying the importance of this law in teaching. in the municipality where the majority of its population is black. As methodological strategies, a bibliographic review and a script of interviews with teachers responsible for the subjects of geography, history and arts, and pedagogical coordinators, were defined. The most evident result in schools is the lack of knowledge of the aforementioned law and the lack of training for teachers on the issue pointed out by the law.